A clinical profile of ocular morbidities at a rural health and training centre in Goa - Cacodcar, Jagadish A.; Usgaonkar, Ugam; Raiturcar, Tanvi Poy (International Journal Of Community Medicine And Public Health, 2018)
Background: Many studies have been conducted in the past to study the profile of ocular morbidities in rural areas in different States in India; however such a study was lacking in Goa. Methods: A case series titled, “A clinical profile of ocular morbidities at a Rural Health and Training Centre in Goa”, was conducted between January to March 2018, after Institutional ethical committee approval. The study population included 200 patients residing in households registered under the Rural Health and Training Centre (RHTC) located at Mandur, who attended the Ophthalmology speciality outreach clinic. After informed consent, patients were interviewed based on a pre-tested proforma. Socio-demographic details and history was obtained and a detailed ophthalmic examination was done. Results: 47.5% were between 41-60 years of age, 49.5% used coal, wood or cow dung as fuel; 26.5% were illiterate or had completed primary schooling. 63% had no visual impairment, visual impairment grade 1 and 2 was present in 10% and 19.5% respectively.7.5% were grouped as blind. 55% had refractive errors, 9.5% had corneal opacities, 33% cataract, 4.5% glaucoma, 7% optic atrophy, 7% retinal and macular involvement. Conclusions: 55% of the participants had refractive errors, 9.5% had corneal opacities, 33% had cataract; 33% of whom were illiterates and 30% were those using coal, wood or cow dung as fuel, suggesting lower socio economic background. The high percentage of patients with corneal opacities and cataract was probably due to lower socio economic status, illiteracy and lack of awareness about ocular problems.